Simulating turbulence–radiation interactions using a presumed probability density function method. (June 2018) - Ren, Tao; Modest, Michael F.; Haworth, Daniel C.
Highlights: TRI are studied using a presumed-PDF methodtogether with a PMC-LBL radiation model. An efficient wavenumber selection scheme isproposed for the PMC-LBL model with TRI. Impact of absorption coefficientself-correlation is investigated. Abstract: In turbulent combustion, the turbulent fluctuations of temperature and species concentrations have strong effects on chemical and radiative heat sources. Turbulence–chemistry interactions (TCI) and turbulence–radiation interactions (TRI) create a set of "closure" problems when the governing partial differential equations are averaged. The presumed probability distribution function (presumed-PDF) method assumes a form of probability distribution function to close the chemical source term. The emphasis of this work is developing a high-fidelity radiation model that works in tandem with combustion models that use the presumed-PDF method to close the turbulent source terms. A finite volume based photon Monte Carlo method with a line-by-line spectral model is applied with the presumed-PDFs of mixture fraction, scalar dissipation rate and enthalpy defect to account for TRI effects. An efficient wavenumber selection scheme is proposed for the line-by-line photon Monte Carlo method considering TRI. The model is validated with one-dimensional exact line-by-line solutions for different TRI treatments and with a coupled combustion simulation for an open jet flame.